The World Trade Organization in the Context of Free Trade Zones - Abbaspour , Javad; Rostami Far, Ali; Elsan , Mostafa (Legal Studies in Digital Age, 2025)
Free trade zones have been established based on the Law on the Administration of Special Economic Zones of the Islamic Republic of Iran to achieve specific objectives outlined in Article 1 of that law. The World Trade Organization (WTO), in turn, was established based on an agreement ratified by approximately 150 countries in 1995, and Iran holds observer status in this organization. In terms of objectives and outlook, these two entities (WTO and free trade zones) share commonalities in areas such as investment, production, export, import, respect for rights, job creation, the elimination of unemployment, and the removal of production subsidies. However, they also have fundamental differences in their structure, organization, and scope of operation. In pursuit of their shared goals, actions such as downsizing the government, reducing bureaucracy, facilitating investment, creating infrastructure, utilizing favorable environments, and ensuring political, economic, and social stability are necessary. Conversely, factors such as governmental instability, unfavorable environments, the existence of bureaucracy, failure to employ competent human resources, and the lack of preparation of skilled workforces hinder the achievement of the objectives behind the establishment of free trade zones.